Home Economics for Gender Justice?: A Case for Gender-Differentiated Caregiving Education - Behrends, Jeff (Ethical theory and moral practice, 2017)
Recent calls for reinstituting mandatory home economics education have emphasized its potential to advance gender egalitarian aims. The thought is that, because womens disproportionate performance of caregiving and household labor is partially caused by gender socialization that better prepares women than men for such work, we can disrupt gender inegalitarian work distributions by preparing everyone for the sort of work in question. The curricula envisioned in these calls are gender-neutral, in the sense that they recommend identical educational interventions for all genders. By exploiting a parallel between gender-neutral educational policies and gender-neutral family leave policies, we argue first that gender-neutral home economics instruction is unlikely to advance gender egalitarian aims, and may in fact reinforce the very outcomes it is meant to disrupt. However, we further argue that a more radical home economics curriculum could avoid these difficulties. To the extent that we value educational interventions as a possible means for advancing gender egalitarian aims, we have good reason to seriously consider adopting a gender non-neutral program in which all and only boys receive mandatory caregiving instruction.